PENCEGAHAN DAN PENANGANAN MALARIA DI DESA CISEREH KECAMATAN TIGARAKSA - Yeyen Desiar Firdasari; Neng Yulianti; Alpian Jayadi; Antonius Rino Vanchapo; Antonia Helena Hamu (Bajang Institute, 2023)
Malaria cases are still a major health problem in the world, especially in countries with tropical climates such as Africa, America, Asia, malaria cases are not due to high cases because malaria cases fluctuate, causing death in endemic areas or not endemic area. Method: using qualitative, lectures to an audience of 40 Cisereh villagers and conducting discussions with the audience. Result: community service that prevention of malaria is carried out by spraying the house (fooging) has never been carried out because it is the duty of the health person or the local health center and the community does not have the tools, what is done is only using mosquito coils or mosquito lotion just. Analisis: From the results of socialization, respondents understand the importance of malaria prevention and handling by maintaining the cleanliness of the local environment, want to direct speakers to wear long clothes when going out of the house and use mosquito repellent lotion, and want to use ITN mosquito nets. Conclusion: Malaria is the highest cause of mortality and morbidity in the world for both toddlers and adults, or all ages and the cause is the bite of the Anopheles mosquito, therefore it is important for us to implement environmental hygiene. should strengthen malaria control strategies such as socializing insecticide-treated nets (ITN), recommending the use of ITNs, and increasing public awareness about malaria transmission